Creative Economy as a Driver of Economic Growth in the Digital Era - Tri Martial; T. Arief Pahlevi Pasha; Rudy Badrudin; Gabriel Amadeus Sitompul (Nomico, 2024)
The creative economy has become a strategic sector in supporting economic growth in the digital era. This research aims to explore the opportunities and potential of the creative economy through digitalization and the challenges faced in developing this sector. This study uses a qualitative study method, with in-depth interviews and observations as data collection techniques to explore the experiences, strategies, and obstacles faced by business actors. The results show that digitalization plays an important role in expanding market reach, improving operational efficiency, and driving innovation. Business actors utilize e-commerce, social media, and digital applications to promote creative products and interact directly with consumers effectively. However, this success still faces challenges, including limited internet infrastructure and low digital literacy among small and medium business actors. Appropriate policy support and increasing digital literacy are key in overcoming these obstacles. This research concludes that with collaboration between the government, the private sector, and the community, the creative economy in Indonesia has great potential to become a key pillar of sustainable economic growth and strengthen competitiveness in the global market.